Benefits of Neuroeconomic Modeling: New Policy Interventions and Predictors of Preference - Krajbich, Ian; Oud, Bastiaan; Fehr, Ernst (American Economic Review, 2014)
Neuroeconomics strives to use knowledge from neuroscience to improve models of decisionmaking. Here we introduce a biologically plausible, drift-diffusion model that is able to jointly predict choice behavior and response times across different choice environments. The model has both normative and positive implications for economics. First, we consistently observe that decisionmakers inefficiently allocate their time to choices for which they are close to indifference. We demonstrate that we can improve subjects' welfare using a simple intervention that puts a time limit on their choices. Second, response times can be used to predict indifference points and the strength of preferences.